AN IMPACT ASSESSMENT OF EFFLUENT FROM THE WATER TREATMENT PLANT PINEDO TO SUSTAIN THE ALBUFERA NATURAL PARK - Novika Rukka; Ton van der Linden; Mathilde de Jongh; Luytzen Woudstra (Fakultas Kehutanan UNIPA, 2019)
The aim of this research is to elaborate of the impacts on the use of the effluent of the water treatment plant Pinedo in the North of Albufera Natural Park in Valencia, Spain. Interviews and observations were conducted, which together created an Impact Assessment. To be able to see the influence of effluent on the water quality, an observation point in the north was compared to another observation point in the south. Besides that, a boat trip was made to observe the water quality on the lake. The result shows that eutrophication occurs as a cosequence of the wastewater from water treatment. Farmers have no choice and are happy to have a constant source. Fishermen have experienced a disastrous change in the seventies, but now see an improvement of the water quality. Environmentalists are most negative about the effluent inflow. The government understands the concerns and wants a higher quality of the effluent, but they do not have means to improve it. Water treatment plant Pinedo recognizes the corncerns either; however, the water quality already meets the requirements. Forecasting the future, everybody is slightly positive. The improvement of the quality of the effluent is a good thing and should carry on.